The Effectiveness of Agile Strategies in Beginner Voter Education: Evidence from the Bantul General Election Commission in the 2024 Regional Head Election - Janan, Dian; Atmojo, Muhammad Eko (Center for Public Policy and Digital Government Universitas Muhammadiyah Yogyakarta, 2026)
First-time voters require effective voter education to develop the knowledge and readiness necessary for meaningful participation in democratic processes. This research investigates the effectiveness of voter education socialization conducted by the Bantul Regency General Election Commission during the 2024 Regional Head Election using Andre Hardjana’s communication effectiveness framework. This research employs a qualitative case study approach to examine communication targets, message content, timeliness, media, message format, and source credibility through interviews, documentation, and literature review. The findings indicate that voter education socialization was generally effective in improving basic electoral literacy among first-time voters. Its effectiveness was supported by appropriate audience targeting, relevant educational content, timely implementation, and the credibility of election organizers. However, limitations in information outreach, activity intensity, language accessibility, and participatory engagement reduced its overall impact. The study argues that communication effectiveness in voter education depends not only on message delivery but also on the accessibility and inclusiveness of communication strategies. This research contributes to the development of political communication and electoral studies by applying Hardjana’s communication effectiveness framework to the context of voter education for first-time voters in local elections. Its novelty lies in identifying how communication effectiveness indicators shape voter education outcomes and in highlighting the need for evaluation mechanisms that measure political awareness beyond electoral participation. The findings provide practical insights for designing more adaptive and effective voter education programs for young voters.